Distribution and ecological status of mangroves in the Nias Islands-North Sumatra Province: Distribution and ecological status of mangroves in the Nias Islands - Ahmad Muhtadi; Zulham Apandy Harahap; Ahyar Pulungan; Zufriwandi Siregar; Elisabet Rosevenny Simaremare; Ani Rahmawati; Wilman Nazara; Khairunnisa (Talenta Publisher, 2023)
The Nias Islands are a group of islands located on the west coast of Sumatra. Nias Island is the main and largest island on the West Coast of Sumatra. Information on the distribution and potential status of mangroves in the Nias Islands has been reported, but it is limited to a narrow area and not yet comprehensive throughout the Nias Islands. This study aims to determine the distribution and ecological status of mangroves in the Nias Islands. The research location was divided into two observation areas, namely 15 points on Nias Island and 23 points on the southern part of Nias. The research was carried out in June 2019 and June 2021. Mangrove sampling was carried out using the